Pengaruh Model Value Clarification Technique (VCT) Terhadap Hasil Belajar PKn Kelas IV di SDN 1 Gelumbang - Febriyani, Siska; Akhbar, M. Taheri; Dedy, Adrianus (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2023)
This study aims to determine the effect of the Value Clarification Technique (VCT) model on thefourth grade Civics learning outcomes at SD Negeri 1 Gelumbang. The research method used is an experimental method of True Experimental Design in the form of Pretest-Posttest Only Control Group Design. The population in this study were fourth grade students of SD Negeri 1Gelumbang. The sample of this study used random sampling, namely IV A and IV C. Datacollection techniques were through tests, observations, and documentation. Based on the results of research and data analysis, it can be seen that the experimental class that was given treatment with Value Clarification Technique (VCT) model had an average final score of 81,03 higher than the average control class that was given treatment without using the Value model Clarification Technique (VCT) is 72,9. The results of testing the hypothesis that tcount = 2,247 and ttablel = 1,675, tcount > ttable (2,247 > 1,675) then Ho is rejected and Ha is accepted, it can be concluded that there is an effect of the Value Clarification Technique (VCT) model on the learning outcomes of Civis Class IV at SD Negeri 1 Gelumbang.